2015
DOI: 10.1016/j.apjtm.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PI3K-mediated autophagy in human osteosarcoma MG63 cells on sensitivity to chemotherapy with cisplatin

Abstract: Up-regulating the autophagy significantly reduced the sensitivity of MG63 cell to chemotherapy with DDP. DDP induced autophagy of MG63 cell and blocked the cell cycle at G1 phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It could be hypothesized that miR-22 is able to inhibit autophagy induced by CDDP and decrease drug resistance via the PI3K/Akt/mTOR pathway both in vivo and in vitro. The results of the present study coincided with the results of a previous study, which revealed which PI3K could be downregulated to inhibit autophagy, leading to suppression of MG63 cell proliferation activity and increasing the sensitivity to CDDP (45). A recent study argued that miR-22-3p enhances the chemosensitivity of gastrointestinal stromal tumor cell lines to CDDP via the phosphatase and tensin homolog deleted on chromosome 10 (PTEN)/PI3K/Akt pathway (26).…”
Section: Discussionsupporting
confidence: 91%
“…It could be hypothesized that miR-22 is able to inhibit autophagy induced by CDDP and decrease drug resistance via the PI3K/Akt/mTOR pathway both in vivo and in vitro. The results of the present study coincided with the results of a previous study, which revealed which PI3K could be downregulated to inhibit autophagy, leading to suppression of MG63 cell proliferation activity and increasing the sensitivity to CDDP (45). A recent study argued that miR-22-3p enhances the chemosensitivity of gastrointestinal stromal tumor cell lines to CDDP via the phosphatase and tensin homolog deleted on chromosome 10 (PTEN)/PI3K/Akt pathway (26).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, autophagy has been reported as a mechanism by which osteosarcoma cells develop resistance to anti-tumor agents, including cisplatin and doxorubicin (27,28). Dysregulation of the p38 MAPK signaling pathway has an important role in tumor development and progression (29).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid luteolin enhanced doxorubicin-induced autophagy in human osteosarcoma U2OS cells through upregulating beclin1, which revealed a synergistic cytotoxicity, leading to U2OS cell death [98]. The 3,4-dihydroxy-9,10-secoandrosta-1,3,5,7-tetraene-9,17-dione (DSTD), a novel androstenedione derivative, inhibited macrophage migration inhibitory factor (MIF) expression in MG-63 and U2OS cells.…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%